Teachers' Perspectives and Practices on Effective Teaching Methods and Strategies at a Primary School in Prishtina - Jahiu, Edona (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2021)
AbstractThis study examined and analyzed nine teachers' teaching practices with children in the sixth to seventh grades of primary school. Effective teaching was discovered in this study to be dependent on three components of a classroom: 1) introduction – linking prior experience to the new issue; 2) sharing/discussing the primary topic; and 3) reflection/summarizing the lesson learned and new terms acquired. The findings indicated that students' learning and comprehension appeared to be contingent on the teacher's strategies for collaborating with students and constantly focusing their attention on the lesson (particularly on crucial features), which facilitated students' willingness to volunteer for discussion participation through open questions, constructive feedback, and so forth. Additionally, it provided teachers with insight on how to handle unforeseen classroom circumstances. For instance, numerous